PEMANFAATAN KELIDANG (Artocarpus lanceifolius Roxb.) OLEH MASYARAKAT DI PULAU NANGKA BESAR, KABUPATEN BANGKA TENGAH - Sari Sari; Yulian Fakhrurrozi; Ade Yusni Franata (Department of Biology, Faculty of Agriculture, Fisheries and Biology, University of Bangka Belitung, 2017)
Kelidang is a species belongs to family Moraceae (the jackfruits). Kelidang grow naturally without the cultivation of human beings. Kelidang in Nangka Besar Island is one of the plants which has tree habitus. Kelidang generally used as furniture, making of boat, households and coffin. The purpose of this research was to explore knowledge of Nangka Besar people about kelidang and its use. The research was carried out by using the method of exploratory that included interviews and observations, which was conducted in the hamlet of Nangka Besar Island Tanjung Pura Village District Sungaiselan Central Bangka Regency Province of Bangka Belitung Islands. The results showed that kelidang is one of the plants which has tree habitus and grow naturally without the cultivation of human beings. Kelidang people in Nangka Besar Island take advantage of kelidang stem as the wall of house, board/lath, firewood, making of boat, frames, the furniture and wood/bench, even used as a coffin by Chinese people. The fruit can be eaten. Seeds boiled and roasted peanuts (fried without oil)